Brief postnatal exposure to bisphenol A affects apoptosis and gene expression in the medial prefrontal cortex and social behavior in rats with sex specificity - Drzewiecki, Carly M.; Brinks, Amara S.; Sellinger, Elli P.; Doshi, Aditi D.; Koh, Jessie Y.; Juraska, Janice M. (Neurotoxicology (Park Forest South), 2023)
Bisphenol A (BPA) is an endocrine disruptor found in polycarbonate plastics and exposure in humans is nearly ubiquitous and it has widespread effects on cognitive, emotional, and reproductive behaviors in both humans and animal models. In our laboratory we previously found that perinatal BPA exposure results in a higher number of neurons in the adult male rat prefrontal cortex (PFC) and less play in adolescents of both sexes. Here we examine changes in the rate of postnatal apoptosis in the rat prefrontal cortex and its timing with brief BPA exposure. Because an increased number of neurons in the PFC is a characteristic of a subtype of autism spectrum disorder, we tested social preference following brief BPA exposure and also expression of a small group of genes. Males and females were exposed to BPA from postnatal days (P) 6 through 8 or from P10 through 12. Both exposures significantly decreased indicators of cell death in the developing medial prefrontal cortex in male subjects only. Additionally, males exposed to BPA from P6 – 8 showed decreased social preference and decreased cortical expression of Shank3 and Homer1, two synaptic scaffolding genes that have been implicated in social deficits. There were no significant effects of BPA in the female subjects. These results draw attention to the negative consequences following brief exposure to BPA during early development. •Rat pups were exposed to BPA for 3 postnatal days (P) 6-8.•Exposed males, not females, had less cell death immediately after the exposure.•Exposed males, not females, showed decreases in a social preference task at P15.•Expression of the genes Shank3 and Homer1 at P30 were lower in exposed males.•BPA exposure at P6–8 increased some characteristics of autism in males.